2014
DOI: 10.5152/tjg.2014.8021
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution manometry: Reliability of automated analysis of upper esophageal sphincter relaxation parameters

Abstract: Background/Aims: At present, automated analysis of high-resolution manometry (HRM) provides details of upper esophageal sphincter (UES) relaxation parameters. The aim of this study was to assess the accuracy of automatic analysis of UES relaxation parameters. Materials and Methods: One hundred and fifty three subjects (78 males, mean age 68.6 years, range 26-97) underwent HRM. UES relaxation parameters were interpreted twice, once visually (V) by two experts and once automatically (AS) using the ManoView ESO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Reporting the ICC and/or CCC along with associated 95% confidence intervals is good practice for agreement analysis. The results are reported in both primary (such as reliability analysis of the Microbleed Anatomical Rating Scale in the evaluation of microbleeds [143], automatic analysis of relaxation parameters of the upper esophageal sphincter [144], and the use of signal intensity weighted centroid in magnetic resonance images of patients with discs degeneration [145]) and secondary research studies (systematic review and/or meta-analysis: evaluation of the functional movement screen [146], evaluation of the Manchester triage scale on an emergency department [147], reliability of the specific physical examination tests for the diagnosis of shoulder pathologies [148], etc. ).…”
Section: Diagnostic Tests and Statistical Methodsmentioning
confidence: 99%
“…Reporting the ICC and/or CCC along with associated 95% confidence intervals is good practice for agreement analysis. The results are reported in both primary (such as reliability analysis of the Microbleed Anatomical Rating Scale in the evaluation of microbleeds [143], automatic analysis of relaxation parameters of the upper esophageal sphincter [144], and the use of signal intensity weighted centroid in magnetic resonance images of patients with discs degeneration [145]) and secondary research studies (systematic review and/or meta-analysis: evaluation of the functional movement screen [146], evaluation of the Manchester triage scale on an emergency department [147], reliability of the specific physical examination tests for the diagnosis of shoulder pathologies [148], etc. ).…”
Section: Diagnostic Tests and Statistical Methodsmentioning
confidence: 99%
“…Currently, there are no commercially integrated platforms available for analysis of pharyngeal swallowing, with the exception of the UES [88]. Although there is ongoing work exploring classification models of pharyngeal swallowing similar to those used in oesophageal analysis [89], there is no consensus on optimal measurements of pharyngeal HRM.…”
Section: Pharyngeal Manometrymentioning
confidence: 99%
“…Further, the optimal location for measurement of nadir UES pressure based on waveforms or topographical plots is currently unknown [92]. This finding was mirrored in a study investigating the reliability of an automated analysis of UES pressure [88], with a poor correlation found for UES relaxation duration (correlation coefficient = 0.29; 95% CI 0.15-0.41). These authors concluded that automated analysis of UES relaxation with HRM is similarly not accurate and called for development of novel analysis techniques.…”
Section: Pharyngeal Manometrymentioning
confidence: 99%
See 2 more Smart Citations